Newly identified active faults in the Pollino seismic gap, southern Italy, and their seismotectonic significance. (January 2017) - Brozzetti, Francesco; Cirillo, Daniele; de Nardis, Rita; Cardinali, Mauro; Lavecchia, Giusy; Orecchio, Barbara; Presti, Debora; Totaro, Cristina
Abstract: The following is a geological study of a Quaternary and active normal fault-system, which crops out in the Pollino area, a seismogenic sector of the Southern Apennines, Italy. From 2010 to 2014, this area was affected by long lasting seismic activity characterized by three major events which occurred in May 2012 (Mw 4.3), in October 2012 (Mw 5.2) and in June 2014 (Mw 4.0). The integration of structural-geological data with morpho-structural and remote sensing analyses, led to define the geometry, the kinematics, the cross-cutting relationships and the slip rates of the inferred active fault segments within and near the epicentral area. We reconstructed an asymmetric extensional pattern characterized by low-angle, E and NNE-dipping faults, and by antithetic, high-angle, SW- to WSW-dipping faults. The geometry of the faults at depth was constrained using high-resolution hypocenter distributions. The overall system fits well with the deformation field obtained from focal mechanisms and geodetic data. Comparing the fault pattern with the time-space evolution of the Pollino seismic activity, we identified the seismogenic sources in two, near-parallel, WSW-dipping faults, whose seismogenic potential were assessed. The peculiar perpendicular-to-fault-strike evolution of the seismic activity, is discussed in the frame of the reconstructed seismotectonic model. Highlights: Several previously unidentified active faults are highlighted within a seismic gap. An asymmetric Quaternary normal fault-system is reconstructed for Northern Calabria. High-resolution geologic and seimologic dataset lead to decipher seismogenic faults. Confinement of seismogenic faults causes a peculiar evolution in time of seismicity.